Hak dan Status Hukum atas Anak dalam Putusnya Perkawinan Campuran ditinjau berdasarkan Hukum Perdata Internasional - Rumi Suwardiyati; Astrid Athina Indradewi (Journal of Contemporary Law Studies, 2026)
Mixed marriage as a consequence of increasing cross-border interactions has generated complex legal implications, particularly concerning the rights and legal status of children following divorce. This study aims to analyze the rights and legal status of children in the dissolution of mixed marriages from the perspective of Private International Law. This research employs a normative legal method using statute, conceptual, and case approaches, with primary legal materials including Indonesian marriage, citizenship, and child protection laws, as well as court decisions. The findings reveal that the legal construction of children’s status in mixed marriages is plural and dynamic due to the intersection of different legal systems, particularly regarding citizenship and custody. Although Indonesian law has accommodated limited dual citizenship and emphasizes the principle of the best interests of the child, its application in judicial practice remains inconsistent. This is evident in court decisions that tend to prioritize domestic legal reasoning (lex fori) without adequately applying Private International Law mechanisms such as choice of law and connecting factors. Furthermore, judicial reasoning has not fully considered progressive approaches such as co-parenting, which are relevant in ensuring the fulfillment of children’s rights in transnational contexts. Therefore, strengthening the application of Private International Law principles and adopting more child-centered and transnationally responsive approaches are essential to ensure legal certainty and optimal protection for children in mixed marriage disputes.